Carbondioxide (CO2) Emission Estimation Caused by Forest Fires on Different Land Covers in South Sumatra Province in 2000-2009 PENDUGAAN EMISI GAS RUMAH KACA AKIBAT KEBAKARAN HUTAN DAN LAHAN PADA BERBAGAI TIPE TUTUPAN LAHAN DI PROVINSI SUMATERA SELATAN - Bambang Hero Saharjo; Erianto Indra Putra; Nursyamsi Syam (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Forest fire has became serious problem and affected to forest balance and bring negative impact for ecology, economy, and political aspects. Therefore, information about land and forest fire based on hotspot are needed as well as carbondioxide emission that released, especially in area that has vulnerability of forest fire, such as South Sumatra Province. The aims of this research are to calculating hotspot in South Sumatra as indicator of land and forest fire, to estimating burned area based on hotspot data, and to calculating carbondioxide (CO2) emission that released from burnt area on different land covers. This research was conducted from July to September 2012 at Forest Fires Laboratory, Department of Silviculture, Faculty of Forestry, Bogor Agricultural University. The data used in this research are MODIS hotspot data from Fire Information Resources Management System (FIRMS), precipitation data from Center of Meteorology Climatology and Geophysics (BMKG), and land covers map of South Sumatra from Roundtable on Sustainable Palm Oil (RSPO). The result showed that the widest burned area in South Sumatra Province was in dry cultivation land which covered by shrub amounted to 6 172 ha (2000), 61 836.81 ha (2005), and 127 259.53 ha (2009). The highest carbondioxide emission was released from dry cultivation land which covered by shrub on mineral land amounted to 52 475.73 ton (2000), 524 417.17 ton (2005), and 1.071.972,41 ton (2009). While the highest carbondioxide emission as result from land covers changed was from cultivation land which covered by shrub amounted to 3.078.899.73 ton (44.52%) and 20 443 299.85 ton (50.60%).Key words: carbondioxide emission, land and forest fire, land covers